Implementation of Income Tax on Third Party Services at PT. Taspen (Persero) Manado - Kroma, Mutiara Pertiwi; Runtu, Treesje; Rondonuwu, Sintje (Formosa Journal of Applied Sciences, 2024)
Tax provisions for third-party services in Indonesia are regulated by various tax regulations, including the Income Tax Act. The main points highlighted in this study include Articles 21, 23, and Article 4(2) on Income Tax. This study aims to investigate and examine how income tax is applied to third party service fees. This study was conducted in PT. Taspen (Persero) in Manado. This study used primary and secondary data types using a qualitative method of descriptive analysis. The results show that PT has high income tax on third-party services. Taspen targets Articles 21, 23 and Article 4(2) of the Income Tax Act. The calculations and deductions adhere to current regulations, with withholding rates of 2.5% and 5% for Article 21, 2% for Article 23, and 10% for Article 4, paragraph 2.